2006
DOI: 10.1074/jbc.m600472200
|View full text |Cite
|
Sign up to set email alerts
|

Analogs of Insulin-like Peptide 3 (INSL3) B-chain Are LGR8 Antagonists in Vitro and in Vivo

Abstract: Insulin-like peptide 3 (INSL3) is a member of the insulin superfamily that plays an important role in mediating testes descent during fetal development. More recently, it has also been demonstrated to initiate oocyte maturation and suppress male germ cell apoptosis. These actions are mediated via a specific G-protein-coupled receptor, LGR8. Little is known regarding the structure and function relationship of INSL3, although it is believed that the principal receptor binding site resides within its B-chain. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
68
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 42 publications
1
68
0
Order By: Relevance
“…Therefore, it is likely that there is a different mechanism for secondary binding to the TM exoloops and that this secondary binding site influences overall binding affinity. Further evidence for this concept is the lack of RXFP1 binding activity of B chain-only analogs of H2 relaxin (38), whereas similar B-chain analogs of INSL3 bind to RXFP2 and act as antagonists (21). Interestingly, the behavior of the truncated H2 analogs is similar on RXFP1 and RXFP2, albeit with lower affinity and activity on RXFP2, suggesting that H2 relaxin activates RXFP2 in an "RXFP1-like" manner.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, it is likely that there is a different mechanism for secondary binding to the TM exoloops and that this secondary binding site influences overall binding affinity. Further evidence for this concept is the lack of RXFP1 binding activity of B chain-only analogs of H2 relaxin (38), whereas similar B-chain analogs of INSL3 bind to RXFP2 and act as antagonists (21). Interestingly, the behavior of the truncated H2 analogs is similar on RXFP1 and RXFP2, albeit with lower affinity and activity on RXFP2, suggesting that H2 relaxin activates RXFP2 in an "RXFP1-like" manner.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, we have recently demonstrated that the INSL3 B-chain interacts with specific residues in the RXFP2 receptor LRRs (19 (20). Importantly, B-chain-only INSL3 peptides can bind to the primary binding sites in the LRRs but do not activate the receptor (21). These peptides are low affinity antagonists and highlight that the A-chain is required for receptor activation.…”
mentioning
confidence: 99%
“…Analogs of INSL3 with modifications in the B-chain at positions 25 and 27 have shown that Trp 27 is essential for characteristic INSL3 activity (13). More recently, our demonstration, that B-chain-only INSL3 peptides can bind to the primary ligand binding site in the ectodomain of LGR8 and act as antagonists (12), has highlighted that the B-chain contains the essential residues for primary binding. It has also enabled a detailed structure-activity relationship study of analogs of the linear peptide to be undertaken.…”
mentioning
confidence: 90%
“…It has also enabled a detailed structure-activity relationship study of analogs of the linear peptide to be undertaken. The results showed that the minimum length required for binding was residues 11-27 and confirmed the critical importance of the Trp 27 residue (12). On the basis of this information and to more precisely map the primary LGR8 receptor binding domain of human INSL3, we undertook its solution structure determination and correlated this with the LGR8 binding activation of INSL3 analogs with selected alanine substitutions in the B-chain.…”
mentioning
confidence: 99%
See 1 more Smart Citation